Corporate Social Responsibility Sebagai Variabel Moderating Kinerja Keuangan Dengan Nilai Perusahaan - Janan, Muhammad Fathul; Mawardi, M. Cholid; Anwar, Siti Aminah (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research aims to analyze the influence of Corporate Social Responsibility (CSR) as a moderating variable on the relationship between financial performance and company value in banking companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The data collection method used is the documentation method using banking company financial report data obtained from the official website of the Indonesia Stock Exchange. The research sample was 11 banking companies. Sampling from the population uses purposive sampling technique. The results of this research using multiple linear regression show that financial performance as proxied by ROA has a significant positive effect on company value, CSR has a significant negative effect on company value, and CSR disclosure as a moderating variable of financial performance has an insignificant negative effect on company value.Keyword : Financial performance, corporate social responsibility, and company value.